Long combination vehicles overtaking cyclists: a field study in regular traffic - Kircher, Katja; Sandin, Jesper (Traffic Safety Research, 2025)
Increased cycling, also in rural areas, is important for transitioning to a more sustainable transport system. Also, long combination vehicles (LCVs), in Sweden labelled high-capacity transport (HCT; up to 34.5 m, the previous limit was 25.25 m) can contribute to this goal. If granted access to a larger share of the road network, those trucks can be used more effectively. However, cycling and other active transport on those roads may be negatively impacted. To investigate direct and indirect effects on cyclists when LCVs are using the same road, a study was conducted in real traffic. Nineteen experienced road cyclists rode on a 5 km long rural road segment. Three trucks of different lengths were driven along the same route, instructed to overtake the cyclists where possible and with a full lane change. This generated 175 overtakes by the trucks and 607 overtakes by other traffic. The cyclists reported the overtakes with the trucks to feel safe and found the length of the truck not to be relevant if a full lane change was made while overtaking. The trucks needed more time to overtake than other traffic, and they also waited longer for an overtaking opportunity. In a car-following situation, the clearance of the following vehicles was influenced by the lead vehicle, making it especially important for heavy vehicles to give cyclists a wide berth. Pending further investigations, the conclusion is that for cyclists to feel safe, a full lane change when overtaking should be standard procedure not only for LCVs, but for motorised traffic in general.